Literature Study: Analysis of Polygamy Factors in Men - Mufarochah Mufarochah; Nafan Tarihoran; Asfandi Asfandi (Eduvest - Journal of Universal Studies, 2025)
This research aims to determine the underlying factors in men who are polygamous. This research uses a literature study method to look for aspects that underlie men's desire to carry out polygamy, using a data accumulation scheme via Mendeley and Google Scholar to access journals and scientific works. A literature search was carried out using the keywords "polygamy" and "Factors" with vulnerabilities in 2015-2024. Keywords are chosen because the themes are related to the topic and are relevant for the last 10 years and the data is up to date. Based on the search, 17,990 articles were found with the research article type, and only 4 of the most relevant articles were selected. The results of previous research and literature studies explain that the factors for polygamy in men are socio-cultural factors, religious factors, psychological factors, educational factors, economic factors.